Autism is associated with interindividual variations of gray and white matter morphology - Mei, Ting; Forde, Natalie J.; Floris, Dorothea L.; Dell’Acqua, Flavio; Stones, Richard; Ilioska, Iva; Durston, Sarah; Mößnang, Carolin Ulrike; Banaschewski, Tobias; Holt, Rosemary J.; Baron-Cohen, Simon; Rausch, Annika; et al. (Biological psychiatry. Cognitive neuroscience and neuroimaging, 2023)
Background - Although many studies have explored atypicalities in gray matter (GM) and white matter (WM) morphology of autism, most of them relied on unimodal analyses that did not benefit from the likelihood that different imaging modalities may reflect common neurobiology. We aimed to establish brain patterns of modalities that differentiate between individuals with and without autism and explore associations between these brain patterns and clinical measures in the autism group. - Methods - We studied 183 individuals with autism and 157 nonautistic individuals (age range, 6-30 years) in a large, deeply phenotyped autism dataset (EU-AIMS LEAP [European Autism Interventions—A Multicentre Study for Developing New Medications Longitudinal European Autism Project]). Linked independent component analysis was used to link all participants’ GM volume and WM diffusion tensor images, and group comparisons of modality shared variances were examined. Subsequently, we performed univariate and multivariate brain-behavior correlation analyses to separately explore the relationships between brain patterns and clinical profiles. - Results - One multimodal pattern was significantly related to autism. This pattern was primarily associated with GM volume in bilateral insula and frontal, precentral and postcentral, cingulate, and caudate areas and co-occurred with altered WM features in the superior longitudinal fasciculus. The brain-behavior correlation analyses showed a significant multivariate association primarily between brain patterns that involved variation of WM and symptoms of restricted and repetitive behavior in the autism group. - Conclusions - Our findings demonstrate the assets of integrated analyses of GM and WM alterations to study the brain mechanisms that underpin autism and show that the complex clinical autism phenotype can be interpreted by brain covariation patterns that are spread across the brain involving both cortical and subcortical areas.
Online verfügbar: 6. September 2022, Artikelversion: 6. November 2023
EU-AIMS LEAP group: Jan K. Buitelaar, Sarah Baumeister, Daniel Brandeis, Andreas Meyer-Lindenberg, Heike Tost [und viele weitere]
Gesehen am 06.08.2024